XRCC3 Thr241Met polymorphism and clinical outcomes of NSCLC patients receiving platinum-based chemotherapy: a systematic review and meta-analysis. - Xiao-yong Shen; Fan-zhen Lu; Yun Wu; Li-ting Zhao; Zhi-feng Lin (PLoS ONE)
Introduction X-ray repair cross-complementing protein 3 (XRCC3) is an essential gene involved in the double-strand break repair pathway. Published evidence has shown controversial results about the relationship between XRCC3 Thr241Met polymorphism and clinical outcomes of non-small cell lung cancer (NSCLC) patients receiving platinum-based chemotherapy. Methods A systematic review and meta-analysis was performed to evaluate the predictive value of XRCC3 Thr241Met polymorphism on clinical outcomes of advanced NSCLC receiving platinum-based chemotherapy. Response to chemotherapy, overall survival (OS) and progression-free survival (PFS) were analyzed. Results A number of 11 eligible studies were identified according to the inclusion criteria. Carriers of the variant XRCC3 241Met allele were significantly associated with good response to platinum-based chemotherapy (ThrMet/MetMet vs. ThrThr: OR  = 1.509, 95% CI: 1.099-2.072, Pheterogeneity  = 0.618). The XRCC3 Thr241Met polymorphism was not associated with OS (MetMet vs. ThrThr, HR  = 0.939, 95% CI:0.651-1.356, Pheterogeneity  = 0.112) or PFS (MetMet vs. ThrThr, HR  = 0.960, 95% CI: 0.539-1.710, Pheterogeneity  = 0.198). Additionally, no evidence of publication bias was observed. Conclusions This systematic review and meta-analysis shows that carriers of the XRCC3 241Met allele are associated with good response to platinum-based chemotherapy in advanced NSCLC, while the XRCC3 Thr241Met polymorphism is not associated with OS or PFS.